2022
DOI: 10.3390/met12050825
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Quality Monitoring of Laser Cladding Process on Rail Steel by an Infrared Camera

Abstract: Laser cladding is considered to be a highly complex process to set up and control because it involves several parameters, such as laser power, laser scanning speed, powder flow rate, powder size, etc. It has been widely studied for metal-part coating and repair due to its advantage in controllable deposited materials on a small target substrate with low heat-affected distortion. In this experiment, laser cladding of U75V and U20Mn rail steels with Inconel 625 powder was captured by an infrared camera with imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…One such method that has been explored is the single-factor experiment, which analyzes the individual impact of variables. The methodology reveals that increasing laser power directly affects the laser spot, melt pool area, cladding height, and width increase [22,23]. Additionally, it has been observed that the cladding width, depth, and height tend to decrease as the laser beam diameter increases [24], and that the cladding depth decreases with an increase in gas supply [25].…”
Section: Introductionmentioning
confidence: 94%
“…One such method that has been explored is the single-factor experiment, which analyzes the individual impact of variables. The methodology reveals that increasing laser power directly affects the laser spot, melt pool area, cladding height, and width increase [22,23]. Additionally, it has been observed that the cladding width, depth, and height tend to decrease as the laser beam diameter increases [24], and that the cladding depth decreases with an increase in gas supply [25].…”
Section: Introductionmentioning
confidence: 94%
“…Among them, the more studied parameters are the laser power, powder feeding rate, and scanning speed [55][56][57][58]. Pornsak et al [59] observed the cladding process in real time by using an infrared camera with image analysis software. The results showed that the laser spot, melt pool area, cladding height, and width all increased with increasing laser power.…”
Section: Single-factor Experimentsmentioning
confidence: 99%
“…(a) Effect of different laser powers on the melt pool. Reprinted from [59]. (b) Fracture toughness and fracture energy of coatings at different laser powers.…”
Section: Figurementioning
confidence: 99%
“…However, it is difficult to achieve on-line monitoring of all influencing factors, resulting in the failure to accurately monitor the coating quality. At present, scholars have carried out much research on the on-line monitoring technology of coating quality in the laser cladding process [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…𝐿 * ℎ * 𝑠𝑖𝑛𝛽 𝑙 * 𝑠𝑖𝑛𝛼 ℎ * 𝑠𝑖𝑛 𝛼 𝛽 (7) In Expression (7), the optical structure parameters L, l, α, and β are constants in actual applications, and the imaging spot displacement h can be calculated by the measurement system. Therefore, the height z of all points on the coating surface can be calculated.…”
mentioning
confidence: 99%